Play Time - Julia Donaldson (Macmillan, 2006)
From the best-selling and much-loved author of THE GRUFFALO and other classic picture books, eleven fun-to-act short plays for primary-aged children (Key Stage 1 and Key Stage 2) complete with helpful, simple guidance on target age, running time and cast! Ranging from adaptations of traditional tales (eg, the legend of Persephone and Three Billy Goats Gruff) to original and contemporary short plays, Julia Donaldson has produced an entertaining, simple, satisfying play collection.
Keywords: Play, Drama; Play -- Play; Drama -- Drama